Respon Pertumbuhan dan Hasil ‎Ciplukan (Physalis peruviana L.) dengan Pemberian ‎Pupuk Petroganik dan POC Sabut Kelapa - Rofi’, Adib Ihsanur; Pratiwi, Ambar (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Continuous application of inorganic fertilizers can reduce soil fertility due to a decrease in its physical, chemical and biological properties. The application of a combination of petroganic fertilizers and POC coconut coir is expected to be able to improve soil properties, so as to optimize plant growth and fruit, especially ciplukan (Physalis peruviana L.). This study aims to analyze the growth and yield of ciplukan (Physalis ‎peruviana L.) by administering various combinations of concentrations of petroganic fertilizer and coco coir POC, and to determine the most optimal combination for ciplukan growth and yield. Sasi Kirana Green House, Purworejo, Hargobinangun, Pakem, Sleman Regency, as well as the Ahmad Dahlan University Botanical Laboratory from March 2022 to June 2022. The research method used was a Completely Randomized Design (CRD) of two variables, in the form of petroganic fertilizer (P0 : 0g, P1: 90g and P2: 180g) and POC coconut fiber (K0: 0%, K1: ‎‎10% and K2: 20%) with 3 repetitions. The dependent variables were plant height, number of leaves, number of branches, crown wet and dry weight, number of fruit, fruit diameter and fruit weight. Data were analyzed by ANOVA parametric test and DMRT follow-up test, or Friedman's non-parametric test. The results showed that the higher the combination of petroganic and POC concentrations of coco coir, the higher the growth and yield of ciplukan. Treatment I (180 g of petroganic and 20% POC concentration) gave significantly different results for all parameters, namely: 1) plant height (192.67 cm); 2) number of leaves (242.33 leaves); 3) number of branches (44.67); 4) crown wet weight (309.33 g); 5) shoot dry weight (58.00 g); 6) number of fruit per plant (66.67 fruit); 7) fruit diameter (13.83 mm); and 8) fruit weight (1.87 g). The conclusions of this study indicate that the application of petroganic and POC coconut coir can increase the growth of ciplukan plants, with the most optimal growth response shown in treatment I (administration of 180g petroganic and ‎20% POC concentration).